Analisis Ergonomi Pada Proses Mesin Tenun Dengan Pendekatan Subjektifitas Pada PT Industri Sandang Nusantara Unit Makateks Makassar - Hamdani Kubangun (Industrial Engineering Study Program, Pattimura University, 2010)
o reveal the workers comfort in doing the job activity on the loom, it is necessary to know standard output produced by the workers during a workday, the energy consumption required in work activities that can increase productivity and examine the complaints and sense of fatigue on the weaving machine operators. Results of processing of standard working hours operating time to complete 60 meters of plastic sacks subjectivity takes 69.79 minutes. And heart rate (physiological performance) before work will be conducted comparisons of the energy when the operator works with estimated energy expenditure 2.3 kcal / min from the results of this comparison is the average energy expenditure has been insufficient demand service or standards issued by Lehman. This is caused by conditions that are not too many movements such as ergonomic work and the workload that must be borne by the body especially the legs, hands, arms and shoulders.